2006
DOI: 10.1007/s00277-006-0193-2
|View full text |Cite
|
Sign up to set email alerts
|

The hyper-CVAD–rituximab chemotherapy programme followed by high-dose busulfan, melphalan and autologous stem cell transplantation produces excellent event-free survival in patients with previously untreated mantle cell lymphoma

Abstract: The hyper-CVAD + rituximab (R) programme consists of fractionated cyclophosphamide, vincristine, doxorubicin and dexamethasone + R alternating with high-dose methotrexate + cytarabine (HD MTX/ARA-C) + R. This regimen, when used as initial therapy for patients under 65 years of age with previously untreated mantle cell lymphoma (MCL), results in remission rates of > 85% with a median event-free survival (EFS) of > 50 months, but with a pattern of continuous relapse out to 60 months. We performed a study of hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 14 publications
0
41
0
Order By: Relevance
“…Whether the addition of stem cell transplantation to the described intensive regimen can improve survival is yet to be determined. Ritchie et al (2007) retrospectively studied a small cohort of 13 patients treated with R-hyperCVAD/R-MA followed by autologous SCT and reported a 92% OS and EFS, with a median follow-up of 3 years, on. Another retrospective study (Vose et al, 2006) reported on 38 patients who received HyperCVAD/MA with or without rituximab and who achieved a PFS of 78% at a median follow up of 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the addition of stem cell transplantation to the described intensive regimen can improve survival is yet to be determined. Ritchie et al (2007) retrospectively studied a small cohort of 13 patients treated with R-hyperCVAD/R-MA followed by autologous SCT and reported a 92% OS and EFS, with a median follow-up of 3 years, on. Another retrospective study (Vose et al, 2006) reported on 38 patients who received HyperCVAD/MA with or without rituximab and who achieved a PFS of 78% at a median follow up of 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…The first is the introduction of the chimeric anti-CD20 antibody rituximab, 17 which in combination with chemotherapy has improved the results of both frontline and salvage treatments for MCL. 9,18,19 The most successful combination is the rituximab and hyper-cyclophosphamide, vincristine, adriamycin, and dexamethasone program (R-hyper-CVAD), 20,21 which is capable of achieving CR rates of up to 90% in the frontline setting, with a prolonged 5-year failure-free survival of 60% in younger patients. 22 These results appear at least equivalent to that of autologous SCT in the era before rituximab.…”
Section: Introductionmentioning
confidence: 99%
“…6,[9][10][11] The superior outcome of patients transplanted in CR1 has been a consistent finding in most reported series, and argues for the application of high-dose therapy with autologous HPCT as part of the primary treatment. 5,[12][13][14][15][16] Nevertheless, it remains unclear whether autologous HPCT is actually curative, and the optimal timing of transplantation remains a point of debate.…”
Section: Introductionmentioning
confidence: 82%
“…The addition of rituximab to cytotoxic chemotherapy regimens has improved the response rates, but the impact on longterm survival remains to be demonstrated. 3,4 Aggressive regimens, such as hyper CVAD (cyclophosphamide, vincristine, doxorubicin and dexamethasone) plus rituximab, consistently produce high response rates, [5][6][7][8] and the followup to date appears promising.…”
Section: Introductionmentioning
confidence: 99%